2013
DOI: 10.1080/17470218.2012.658820
|View full text |Cite
|
Sign up to set email alerts
|

How strongly do word reading times and lexical decision times correlate? Combining data from eye movement corpora and megastudies

Abstract: We assess the amount of shared variance between three measures of visual word recognition latencies: eye movement latencies, lexical decision times and naming times.After partialling out the effects of word frequency and word length, two well--documented predictors of word recognition latencies, we see that 7--44% of the variance is uniquely shared between lexical decision times and naming times, depending on the frequency range of the words used. A similar analysis of eye movement latencies shows that the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
74
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 51 publications
10
74
1
Order By: Relevance
“…In an interesting study, Kuperman et al (2012) found little shared variance between eye movement data from the Dundee corpus (Kennedy & Pynte, 2005) and reaction time data from the ELP (Balota et al, 2007). Our data could also be exploited by similar studies for comparing monolingual data from the corpus to, for instance, the BLP , the L1 bilingual data to the DLP (Keuleers, Diependaele, et al, 2010), and the L2 bilingual data to a potential future lexicon project in the L2 (which is nonexistent, to date).…”
Section: Avenues For Future Researchmentioning
confidence: 91%
See 2 more Smart Citations
“…In an interesting study, Kuperman et al (2012) found little shared variance between eye movement data from the Dundee corpus (Kennedy & Pynte, 2005) and reaction time data from the ELP (Balota et al, 2007). Our data could also be exploited by similar studies for comparing monolingual data from the corpus to, for instance, the BLP , the L1 bilingual data to the DLP (Keuleers, Diependaele, et al, 2010), and the L2 bilingual data to a potential future lexicon project in the L2 (which is nonexistent, to date).…”
Section: Avenues For Future Researchmentioning
confidence: 91%
“…Both Frank and Bod (2011) and Fossum and Levy (2012) used the Dundee corpus to evaluate their language models concerned with the role of hierarchical mechanisms in sentence processing. Kuperman et al, (2012) used both the megadata of the ELP (Balota et al, 2007) and the Dundee corpus (Kennedy & Pynte, 2005) to correlate lexical decision times with natural reading data. Their results showed very low correlations between these measures, implying that these commonly used methods measure, at least to some extent, different processes.…”
Section: Eyetracking Corporamentioning
confidence: 99%
See 1 more Smart Citation
“…The discrepancy of the effects in the two tasks across experiments (i.e. inhibition vs. facilitation) also points at certain constraints for using lexical decision procedures as a proxy for assessing processing mechanisms in normal reading for comprehension (Kuperman, Drieghe, Keuleers, & Brysbaert, 2013; see also Huestegge, Radach, Corbic, & Huestegge, 2009, for similar constraints with respect to single word naming tasks).…”
Section: Discussionmentioning
confidence: 99%
“…Specific reading measures on the critical word were selected in order to observe processes related to lexical access and post-lexical sentential integration. The selected reading measures were: first-fixation duration (duration of first-fixation on the critical word), single-fixation duration (duration of first-fixation when only one fixation was made on the critical region), gaze-duration (summed duration of all fixations made on critical region before the eye left the word for the first time), and total-time on the critical region (for a review of these measures, see Rayner, 1998;Kuperman, 2013).…”
Section: Methodsmentioning
confidence: 99%